2023
DOI: 10.1371/journal.pone.0285413
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA mutations in breast cancer: A Tunisian series

Abstract: Background The aim of this study was to analyze PIK3CA mutations in exons 9 and 20 in breast cancers (BCs) and their association with clinicopathological characteristics. Methods Mutational analysis of PIK3CA exon 9 and 20 was performed by Sanger sequencing in 54 primary BCs of Tunisian women. The associations of PIK3CA mutations with clinicopathological characteristics were analyzed. Results Fifteen exon 9 and exon 20 PIK3CA variants were identified in 33/54 cases (61%). PIK3CA mutations including pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…E542K and E545K on exon 9, encoding the helical domain (HD), and H1047R on exon 20, encoding the kinase domain (KD) [31]. Previous research has indicated that endocrine-resistant PIK3CA-mutant cases may potentially bene t from treatment with PI3K inhibitors, underscoring the signi cance of elucidating the prevalence of PIK3CA mutations among populations to inform potential future avenues in hormone receptor-positive breast cancer treatment [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E542K and E545K on exon 9, encoding the helical domain (HD), and H1047R on exon 20, encoding the kinase domain (KD) [31]. Previous research has indicated that endocrine-resistant PIK3CA-mutant cases may potentially bene t from treatment with PI3K inhibitors, underscoring the signi cance of elucidating the prevalence of PIK3CA mutations among populations to inform potential future avenues in hormone receptor-positive breast cancer treatment [32].…”
Section: Introductionmentioning
confidence: 99%
“…Research underscores the signi cance of analyzing PIK3CA gene mutations due to their association with the onset and progression of breast cancers (BCs). These mutations are detected in 20-40% of BC patients [29,30,32]. Studies suggest that the presence of PIK3CA mutations can negatively impact disease-free survival (DFS) and pathological complete response (pCR) to targeted therapy and chemotherapy in patients with HER2-enriched and triple-negative breast cancer (TNBC) [33].…”
Section: Introductionmentioning
confidence: 99%